SOCIAL ECOFEMINISM IN ESCAPE BY MANJULA PADMANABHAN - Binani, Mansi; Singh, Swati (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study highlights the themes of ecofeminism and dystopia in Manjula Padmanabhan’s novel Escape. The primary goal is to analyse how the novel portrays a society that systematically oppresses women and exploits the environment, reflecting broader concerns of patriarchal control and ecological degradation. The research design includes a critical examination of the narrative structure and thematic elements, drawing from ecofeminist theory to explore the interconnectedness of gender and environmental issues. The methodology involves a close reading of the text, with a focus on character dynamics, particularly the experiences of women in the dystopian setting. The analysis reveals that Padmanabhan’s depiction of a world where women are hunted and nature is ravaged serves as a powerful critique of contemporary societal norms. To concludes that Escape not only highlights the dangers of extreme patriarchal dominance but also advocates for a reconceptualization of human relationships with nature and each other, emphasizing the need for ecological and gender justice.